NOVEL COSMECEUTICAL FORMULATIONS: A BETTER APPROACH TO PHOTOPROTECTION - MOHANTY, SANGEETA; BADHEI, LIPANJALI; PAL, ABHISEK; PANDA, PRITIPADMA (International Journal of Applied Pharmaceutics, 2022)
Using photoprotection, it is possible to prevent UV-induced skin damage and skin cancers. Radiation that falls between visible light and X-rays is defined as ultraviolet. By biological consequences, UVR is classified into five types, UVA, UVB, UVC, Far UV, and Vacuum UV. However, sunscreen functions as an essential device in our accessories of photo protective action, whose goal is to protect us from sunburn and from the harmful effects of ultraviolet radiation. Sunscreens are categorized as systemic and topical, depending on how they are administered. Again, topical sunscreen divides into organic and inorganic sunscreen. Despite the main objective of sunscreen is to be secure, chemically inert, non-toxic and protected against wide-ranging radiation so as to combat photo aging and photocarcinogenesis. But chemical and synthetic sunscreen causes several undesirable effects, which is a matter of concern. Therefore, a better and safer photoprotective agent is needed in sunscreen. In this regard, nanoparticles, or nanoparticulate systems, are becoming increasingly popular as a form of sunscreen for many different reasons, such as boosting SPF and stability, customizing the release profile, and minimizing adverse effects. In this review, the nanoformulation approach of sunscreen has been described, which has more demand than conventional sunscreen, including liposomes, ethosomes, microemulsions, nano-emulgel, solid-lipid nanoparticles, nano-transferosomes, and niosomes which received a lot of attention worldwide. In short, this review provides an outline of novel advent to sunscreen formulations.